2014
DOI: 10.1002/pssr.201409333
|View full text |Cite
|
Sign up to set email alerts
|

Excellent passivation of thin silicon wafers by HF-free hydrogen plasma etching using an industrial ICPECVD tool

Abstract: In this work, hydrogen plasma etching of surface oxides was successfully accomplished on thin (∼100 µm) planar n‐type Czochralski silicon wafers prior to intrinsic hydrogenated amorphous silicon [a‐Si:H(i)] deposition for heterojunction solar cells, using an industrial inductively coupled plasma‐enhanced chemical vapour deposition (ICPECVD) platform. The plasma etching process is intended as a dry alternative to the conventional wet‐chemical hydrofluoric acid (HF) dip for solar cell processing. After symmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Space charge region recombination was ignored in both HF and HPE samples due to minimal damage induced by plasma etching demonstrated in our previous works. [8,9] In addition to dopant type and concentration, all common fitting constants are summarized in Table 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Space charge region recombination was ignored in both HF and HPE samples due to minimal damage induced by plasma etching demonstrated in our previous works. [8,9] In addition to dopant type and concentration, all common fitting constants are summarized in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works, we have shown that conventional diluted hydrofluoric acid (HF) dip as the final cleaning step is not desirable in terms of safety, environment, and fabrication cost. [ 8 ] We further demonstrated that by replacing HF cleaning with the novel hydrogen plasma etching (HPE), minority carrier lifetime can be largely enhanced due to the inclusion of excessive hydrogen particles which provide significant chemical passivation upon subsequent thermal annealing. [ 9 ] However, based on our recent simulation results, the enhanced chemical passivation alone cannot fully account for lifetime improvement compared with samples prepared by conventional HF method; the lifetime increase after annealing is also far more prominent relative to other literature reports.…”
Section: Introductionmentioning
confidence: 99%
“…The vacuum break occurs only when flipping over the wafers. The optimal condition (60 s, 500 sccm) was identified in terms of achieving the highest lifetimes τ eff , which were recorded by QSSPC after a-Si:H passivation and thermal annealing at the optimal temperature of 290°C for 3 min [15], [20]. A total of two samples with high lifetimes τ eff of 2.5 ms (60 s, 500 sccm) and 1.5 ms (90 s, 500 sccm), respectively, were selected for TEM and HAADF-STEM measurements to characterize the a-Si:H/c-Si interface.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, integration of such dry passivation processes into SHJ solar cell fabrication is still challenging because of the difficulty to remove the silicon oxide layer effectively while limiting the H 2 plasma induced damage to the c-Si surface. Up to now, several research groups have worked on this process in an either capacitively [13], [14] or inductively coupled radio-frequency plasma-enhanced chemical vapor deposition (RF-PECVD) reactor [15], [16]. Moreno et al reported a two-step etching process (420 s) using precursor mixtures of silicon tetrafluoride and H 2 to replace the HF dip prior to a-Si:H deposition [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation